Stability of a Dynamical System with Semi-Markov Switchings under Conditions of Stability of the Averaged System - Korolyuk, V. S.; Chabanyuk, Ya. M. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We establish additional stability conditions on the rate of a dynamical system with semi-Markov switchings and on the Lyapunov function for the averaged system.